A rapid agroecological value chain analysis in Kenya - Onyango, Kevin; Ndiwa, Aurillia Manjella; Bolo, Peter Omondi; Wanyama, Rosina; Chege, Christine G.K. (2023)
A rapid assessment of the Green Leave Vegetables (GLV) value chain in the Kiambu Living Landscape shows that huge potential exists for agroecological transition in this region. At the farm level, farmers are already applying selected agroecological principles, such as a decrease in the use of external inputs, crop and economic diversification, biodiversification, and soil management techniques, among others. This is attributed to the presence of several players in the value chain, such as the Kiambu County government, CSHEP, SNV, JKUAT, and PELUM, that have promoted the uptake of agroecological practices in the area. Despite this, the scale of application of these practices is still limited due to factors such as limited knowledge, poor infrastructure, biotic and abiotic stressors, limited access to resources, and lack of policy guidance, among others. For instance, farmers are still using chemical pesticides and fertilizers, especially on exotic vegetables, which are highly susceptible to pests and diseases.